Field reports form for submitting seasonal observations of Iowa birds, Summer 1999, Mark Proescholdt - Proescholdt, Market al (1999)
An annotated list of birds sighted by Mark and Beth Proescholdt. This item was used as supporting documentation for the Iowa Ornithologists' Union Quarterly field report of summer 1999. Epson - sheet feed